IMPLEMENTASI STRATEGI ICE BREAKING DALAM PEMBELAJARAN SEBAGAI UPAYA MENINGKATKAN KONSENTRASI DAN KETERLIBATAN SISWA DI UPTD SDN PEJAGAN 1. - Raudatul Mangfiroh; Fauzi; Izzah Fijriyah; Yustiana Dewi (STKIP Subang, 2026)
This research utilized a descriptive qualitative design aimed at uncovering how ice breaking strategies were executed within classroom learning and how they affected students’ focus and engagement. Conducted in the third grade of UPTD SDN Pejagan 1 Bangkalan during the first semester of the 2025/2026 academic year, the study involved the class teacher and students. Data were obtained through observation, interviews, and documentation, offering a holistic depiction of ice breaking practices. The analysis was carried out using the Miles and Huberman interactive framework encompassing data reduction, display, and interpretation. The study found that ice breaking had yet to be consistently practiced due to the teacher’s limited awareness of activity types appropriate for young learners, though both teacher and students showed enthusiasm for its application. Students reported feeling more focused and enthusiastic after participating in refreshing activities such as simple games, motivational claps, or light stretching exercises. This study concludes that ice breaking has great potential as a learning strategy to enhance students’ concentration and engagement while creating a more enjoyable and interactive learning atmosphere in elementary education.